127k views
5 votes
Differentiating Exponential functions In Exercise,find the derivative of the function. See Example 2 and 3.

f(x) = ex + 1/ex - 1

1 Answer

5 votes

Answer:


(d)/(dx)\left((e^x+1)/(e^x-1)\right)=-(2e^x)/(\left(e^x-1\right)^2).

Explanation:

To find the derivative of the function
f(x)=(e^x+1)/(e^x-1) you must:

Step 1. Apply the Quotient Rule
\left((f)/(g)\right)'=(f\:'\cdot g-g'\cdot f)/(g^2)


(d)/(dx)\left((e^x+1)/(e^x-1)\right)=((d)/(dx)\left(e^x+1\right)\left(e^x-1\right)-(d)/(dx)\left(e^x-1\right)\left(e^x+1\right))/(\left(e^x-1\right)^2)


(d)/(dx)\left(e^x+1\right)=e^x\\\\(d)/(dx)\left(e^x-1\right)=e^x


=(e^x\left(e^x-1\right)-e^x\left(e^x+1\right))/(\left(e^x-1\right)^2)

Step 2. Simplify


\frac{{e^(2x)-e^x-e^(2x)-e^x}}{\left(e^x-1\right)^2} \\\\(-2e^x)/(\left(e^x-1\right)^2)

Therefore,


(d)/(dx)\left((e^x+1)/(e^x-1)\right)=-(2e^x)/(\left(e^x-1\right)^2)

User Sandeep Mukherjee
by
5.5k points